PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DESA BALAM JAYA PADA KANTOR KECAMATAN WAY KENANGA KABUPATEN TULANG BAWANG BARAT - Fevi Lestiana; Andri Irawan (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2012)
District Office District Way Boxwood Bone Garlic is one example of a government agencymust provide services to the community who require paperwork, letters and so on. District OfficeDistrict Way Boxwood Bone Garlic as a government agency tasked with providing public services isalways required to work optimally serve the community. In reality, not all employees Boxwood WayDistrict Office can provide good service to the community, as well as employee morale, not everyemployee has a high morale. It certainly will affect people's satisfaction with services provided theDistrict Office Boxwood Way.The purpose of this study was to determine or measure the influence of communitysatisfaction with quality of service to the Village Balam Jaya at the District Office District BoxwoodBone Onion Way West Based on existing problems, the authors use a simple regression analysis thevalue of R, R2 and adjusted R2 std. Error. The value of correlation coefficient (R) which indicates thelevel of relationship between variables (0.752). Determininasi R2 coefficient (R square) of 0.567.Shows that public satisfaction is influenced by the quality of service while the remaining 56.7%amounting to 43.3% influenced by other factors or variables not examined in this study. Gained4.550 quality of service t count> t table while (dk = n-2 = 97-2 = 95) is equal to 1.658. So 4.550 tcount> t table 1.658, meaning that Ho Ho is rejected and accepted, the conclusion is there isinfluence between service quality to satisfaction Balam Jaya villagers who take care of populationadministration. If the view of probability (sig) of 0.000 <0.05 so Ho rejected and Ha accepted.